2021
DOI: 10.4103/jfmpc.jfmpc_2378_20
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing the treatment of newly diagnosed type 2 diabetes mellitus with combination of dipeptidyl peptidase-4 inhibitors and metformin

Abstract: The expanding burden of Type 2 Diabetes Mellitus (T2DM) in today's world, with respect to incidence, prevalence, and cost incurred, is an existential risk to society. Various guidelines recommend individualization of treatment. This expert opinion aims to review the recent evidences and reach a consensus on the preferable combination therapy for use in newly diagnosed Indian T2DM patients with HbA 1C >7.5%. The core committee included seventeen diabetes specialists. Three statements were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 61 publications
1
1
0
Order By: Relevance
“…20 These findings are in agreement with the ICMR recommendations of routine screening of diabetes in India at 30 years more so in overweight and obese adults. 21 Our study reported a higher prevalence (53.11%) of T2DM in obese or overweight population, which is in concordance with the WHO data, wherein overweight and obesity accounted for 44% of the diabetes cases and the prevalence of obesity-related diabetes is expected to double to 300 million by 2025. [22][23][24] Highlighting this fact has led to the connotation 'diabesity'.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…20 These findings are in agreement with the ICMR recommendations of routine screening of diabetes in India at 30 years more so in overweight and obese adults. 21 Our study reported a higher prevalence (53.11%) of T2DM in obese or overweight population, which is in concordance with the WHO data, wherein overweight and obesity accounted for 44% of the diabetes cases and the prevalence of obesity-related diabetes is expected to double to 300 million by 2025. [22][23][24] Highlighting this fact has led to the connotation 'diabesity'.…”
Section: Discussionsupporting
confidence: 91%
“…Also, American Association of Clinical Endocrinology 2018 consensus statement algorithm recommends metformin plus another agent in patients with HbA1c >7.5% at diagnosis. 21 Metformin and DPP-4 inhibitors were the preferred antidiabetic agents in the newly diagnosed T2DM patients as well as patients with microvascular complications. In this study, at time of diagnosis, 9.2% patients presented with microvascular complications.…”
Section: Discussionmentioning
confidence: 99%